Tax Planning atas Beban Penghasilan pada PT Eagle Golden Energy - Tiara Setra Linuhung; Memen Kustiawan; Ida Farida Adi Prawira (Journal of Financial and Tax, 2024)
This study aims to save tax burden through maximization of expense recognition. The method used is descriptive analysis. Tax planning in this article focuses on maximizing the recognition of CSR expenses, employee training expenses, and post-employment benefit expenses. After the three expenses were recognized, the company's profit before tax decreased by Rp49,037,201,277 and income tax expense decreased by Rp10,788,184,281